Structural Systems Comparison of Simply Supported PSC Box Girder Bridge Equipped with Elastomeric Rubber Bearing and Lead Rubber Bearing - Alvin Kurniawan Santoso; Djoko Sulistyo; Ali Awaludin; Angga Fajar Setiawan; Iman Satyarno; Sidiq Purnomo; Ignatius Harry (Institute of Research and Community Outreach - Petra Christian University, 2022)
This study compares the influence of elastomeric rubber bearing (ERB) as the regular bearing support and lead rubber bearing (LRB) as the seismic isolation device on the seismic performance of a seven-span simply supported prestressed concrete (PSC) box girder bridge, which was analyzed using nonlinear time history analysis (NLTHA) with the OpenSees software. The results showed that the maximum pier responses and damage were smaller in models with LRB than with ERB. The bridge model using ERB occurred the slightest damage at levels II, while the one using LRB was at levels I. In addition, the highest seismic performance level in the model with ERB was at the operational limit. Meanwhile, the seismic performance in the model with LRB was at the fully operational limit. Thus, LRB was a good preference for improving the seismic performance and mitigating the damage due to the seismic excitation with a slender pier.